Moral Logics of Support for Nonviolent Resistance: Evidence From a Cross-National Survey Experiment. (March 2023) - Dahlum, Sirianne; Pinckney, Jonathan; Wig, Tore
An emerging consensus holds that nonviolent resistance campaigns are more successful than violent campaigns, partly because they attract more participants. Yet, we lack an understanding of whether and why nonviolent tactics attracts support. We propose two motivational logics that can explain support for nonviolence: An instrumentalist logic, whereby nonviolent resistance is preferred based on cost-benefit considerations, and an intrinsic logic where nonviolent resistance is preferred because of perceived inherent moral worth. To investigate the motivational pull of these two logics, we conduct a pre-registered survey experiment among more than 5000 respondents across 33 countries in fall 2019. We find that nonviolent tactics strongly increase movement support relative to violent tactics, and that the preference for nonviolence is primarily driven by intrinsic commitments to the moral worth of nonviolent resistance, rather than instrumental considerations.